PERAN GEREJA DI DALAM PEMBANGUNAN TRANSFORMASIONAL CITY: THE ROLE OF THE CHURCH IN TRANSFORMATIONAL CITY DEVELOPMENT - Desire Karo karo; David Ming (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2023)
Abstract: The way a person understands poverty and its causes tends to shape the way a persondeals with it. Most government agencies and most institutions define poverty as a whole based onterminology. If the perception of the material used for the problem of poverty is a completeunderstanding, it is not surprising that the local church is not included in it. The purpose of thisstudy is to find out how Christian understanding of transformational city development is? what isthe role of the church in the development of a transformational city? The method used is descriptiveliterature. The result obtained is that being a Christian is not just a status, but is followed by thecharacter and traits attached to it. The Lord Jesus stated the importance of being salt and light whohave character and nature according to their essence. The church has an extraordinaryresponsibility to be involved in various aspects of life that have an impact in being a blessing andbeing open in the midst of people who do not yet know Jesus Christ (plural).Keywords: Church, Leading Transformational, Civil Society